Faktor yang Mempengaruhi Niat Pembelian Kembali Oleh Konsumen Produk Kecantikan Yang Hanya Dijual Secara Online - Karryn Krisnia Putri; Thomas Thomas; Wira Natanegara; Primidya Kartika Miranda Soesilo (Mahesa Research Center, 2022)
This study aims to further examine the factors that influence Repurchase Intention, where these factors are Brand Personality, Brand Equity, Brand Familiarity, and Word of Mouth. Alongside the development of the market, we found that beauty products that are only sold online and offline have a good role in the e-commerce market to help Indonesia's economic development. We further researched specific beauty products that are only sold online, because there are differences between brands that are only sold online and brands that have offline stores. Then the number of consumers who buy beauty products that are only sold online is increasing every year, so this leads us to the discovery that there is an influence on Repurchase Intention from the Brand Equity and Brand Familiarity factors. Then on Brand Personality and Word of Mouth there is no effect on Repurchase Intention. In this study, we used quantitative methods as our research method, namely using regression which we processed based on results from online surveys. The results of the research that we get are in the form of two variables that affect re-purchase intention, namely brand equity and brand familiarity, while brand personality and word of mouth have no influence on the results of this study.